Trust and trustworthiness of women and men in decision-making processes in conditions of stress - Markowska-Przybyła, Urszula (Zaufanie i wiarygodność kobiet i mężczyzn w procesie podejmowania decyzji w warunkach stresu, 2021)
The article presents research on the influence of stress on making decisions, the importance of which is based on trust and trustworthiness. In particular, it also applies to the gender factor, as research shows that the reactions of women and men are different. The role of women in management processes is constantly growing, and the recognition of the reaction to stressful situations accompanying the decision-making process is noteworthy and little recognized in terms of trust and trustworthiness. The research used the theory-based experiment method and the questionnaire method, which made it possible to assess the intentional-behavioural gap, i.e. the assessment of the convergence of the declaration with the observation; 199 people (students of management) were subject of the study. The research results do not indicate the fragility of trust and credibility in the context of stress, nor do they show significant differences in changes in trust and credibility between women and men in response to stress. However, they indicate the need for the cautious use of the survey tool in the examination of trust and trustworthiness
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 72-86